Optimal Design and Analysis of Conical Magnetic Gear - Seyed Ahamdreza Afsari Kashani (AUT Journal of Electrical Engineering)
Conical machines with a unique conical rotor and stator design have several advantages over electrical machines with traditional designs. The conical shape allows for greater torque and efficiency, which makes these machines ideal for use in heavy machinery and industrial equipment. Besides, their compactness in comparison with traditional machines makes them easier to integrate into manufacturing processes.  Furthermore, since magnetic gears (MGs) have provided a solution to overcoming mechanical challenges and disadvantages of mechanical gears, their development has become a hot research topic in the last few years. Due to asymmetric geometry and special flux paths, the analysis should be modeled in 3-D finite element tools. In this paper, a hybrid structure, named conical MG, is introduced in order to benefit simultaneously from the advantages of radial flux and axial flux structures of MG. This topology can provide more contact surface of permanent magnets (PMs) and, thus, increase the torque density, with a proper design and the optimization of dimensions. The proper shaping of the PMs and providing the correct structure of MG can lead to a high impact on the output characteristics of the system. This design improves the transmission torque by forming the magnetic fields in air gaps. To compare the proposed topology, the optimal design of the model is compared with the conventional radial flux structure using the genetic algorithm and 3-D finite element method to obtain maximum torque density. The results are compared and the superiority of the proposed model is proved.